PENYULUHAN PENGGUNAAN APD PADA KARYAWAN DI PT PAJ TAHUN 2022 - apriana, ana -; Rusli, Kenvin (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Personal Protective Equipment (PPE) is equipment that functions to protect workers from potential accident risks while carrying out their duties. The use of PPE is an important step in efforts to reduce the number of accidents in the workplace. This study aims to eval_uate worker behavior in using PPE at PT PAJ. The study was conducted with an observational analytical approach, involving all employees as a population, while the sample consisted of 50 workers. Based on the results of the study, the majority of workers (88%) have a good level of knowledge, more than half (54%) have a supportive attitude, but most (80%) still do not use PPE completely. Therefore, it is recommended to increase workers' understanding and awareness of the importance of using PPE to prevent work accidents.